Preparation of Carbon Nanotubes by CVD Process over Nanoparticles of Ni-Ce-Zr Mixed Oxides (Journal of Sciences, Islamic Republic of Iran)
Carbon nanotubes (CNTs) were prepared by the catalytic chemical vapor deposition of C2H2 at 550°C in 120 minutes using nanoparticles of Ni-Ce-Zr mixed oxides. The CNTs were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM) and Raman spectroscopy. The results revealed that CNTs with diameter of about 45 nm are obtained. Utilization of Ni-Ce mixed oxides or NiO2 respectively afforded CNTs with helical and curved morphologies and diameters of about 50 and 90 nm. No CNTs were formed either in the absence of catalyst or exclusion of Ni from Ce-Zr mixed oxides. Details of the catalyst type and its impact on CNTs morphologies will be presented.